A conserved RNA polymerase III promoter required for gammaherpesvirus TMER transcription and microRNA processing - Diebel, Kevin W. (Gene, 2014)
Canonical RNA polymerase III (pol III) type 2 promoters contain a single A and B box and are well documented for their role in tRNA and SINE transcription in eukaryotic cells. The genome of Murid herpesvirus 4 (MuHV-4) contains eight polycistronic tRNA-microRNA encoded RNA (TMER) genes that are transcribed from a RNA pol III type 2-like promoter containing triplicated A box elements. Here, we demonstrate that the triplicated A box sequences are required in their entirety to produce functional MuHV-4 miRNAs. We also identify that these RNA pol III type 2-like promoters are conserved in eukaryotic genomes. Human and mouse predicted tRNA genes containing these promoters also show enrichment of alternative RNA pol III transcription termination sequences and are predicted to give rise to longer tRNA primary transcripts.